(untitled) (American Journal of Islam and Society, 1996)
The two books recently authored by Ernest Gellner and Akbar Ahmed on the subject of Islam and postrnodernism have attracted interest among Muslims and non-Muslims. To me, it is a landmark in the continuing dialogue between Islam and the West. Has the rise of postmodernism in western philosophical thought meant an easier accommodation of Islam into contemporary western society, or is Islam intellectually at odds with the epistemological foundations of postmodernism? These are some of the important questions addressed by Gellner and Ahmed. In view of the increasing cultural and intellectual globalization, not to mention the economic side, taking place today, the place of Islam in contemporary thought and society can no longer be safely isolated from "western" thought and culture. Unlike previous encounters, where victory was decided through military confrontations, or in times of peace, where coexistence is maintained through the separation of borders limiting influence and interaction, ours is a time when cultures and civilizations are interlocked. Hence, it is of the utmost importance that Muslims define their thought and philosophical position dearly in relation to the West, if they insist on maintaining their identity and way of life in a world that is increasingly westernized. Part of the Muslim ummah’s legitimacy derives from the sovereignty of its individual nations existing in the world community and from the intellectual strength of its religious and philosophical position. Muslims cannot compromise on that if they are to maintain their viability as an ummah in the contemporary world. Recent intellectual dialogues on Islam and the West, therefore, should acquire an important place in the Musim minds and agenda if they are not to witness the further erosion of Islamic values and beliefs. In view of the importance of the discussions on Islam by Gellner and Ahmed in their recent works, I now tum to an analysis of their books. Gellner on Islam, Rationalism, and Postmodernism As opposed to previous binary polarities in history, Gellner believes that our time is characterized by a competition between three irreducible ...